2009
DOI: 10.9775/kvfd.2010.2802
|View full text |Cite
|
Sign up to set email alerts
|

Bakteriyel Zoonozların Epizootiyolojisinde Potansiyel Risk: Güvercin (Columba livia domestica) Dışkısı

Abstract: SummaryThe purposes of this study were to determine the profile of some Gram-negative bacteria in domestic pigeon intestinal microfl ora and isolated Enterococcus and E. coli strains to some antibiotics resistance were investigated by disc diff usion methods. For this purpose, cloacal swab samples were collected from a total of 215 pigeons from 8 diff erent pigeon-houses, in Kirikkale, Turkey. A total of 180 isolates were obtained from 215 samples and these isolates were identified as 46% E. coli, 10% Enteroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Enrofloxacin, gentamicin, and ciprofloxacin resistance were not detected in any of the pigeon-origin E. coli isolates. Interestingly, these results were found to be consistent with one study that analyzed the antibiotic susceptibility profile of E. coli isolates obtained from domestic pigeons (Columba livia domestica) in Turkey and reported 100% susceptibility to enrofloxacin and gentamicin [67]. Furthermore, Silva et al [62] reported 100% gentamicin susceptibility of pigeon-origin E. coli isolates, which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Enrofloxacin, gentamicin, and ciprofloxacin resistance were not detected in any of the pigeon-origin E. coli isolates. Interestingly, these results were found to be consistent with one study that analyzed the antibiotic susceptibility profile of E. coli isolates obtained from domestic pigeons (Columba livia domestica) in Turkey and reported 100% susceptibility to enrofloxacin and gentamicin [67]. Furthermore, Silva et al [62] reported 100% gentamicin susceptibility of pigeon-origin E. coli isolates, which is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 91%
“…The different isolation rates or diversity of species can be resulted from different breeding facilities, management procedures and environmental factors [2,4,[10][11][12][18][19][20] . The presence of VRE in companion animals is becoming a high clinical concern due to the high transmission risk of VRE via close contact with their owners.…”
Section: Discussionmentioning
confidence: 99%